2016
DOI: 10.1007/s13238-016-0328-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the recognition of phosphorylated FUNDC1 by LC3B in mitophagy

Abstract: Mitophagy is an essential intracellular process that eliminates dysfunctional mitochondria and maintains cellular homeostasis. Mitophagy is regulated by the post-translational modification of mitophagy receptors. Fun14 domain-containing protein 1 (FUNDC1) was reported to be a new receptor for hypoxia-induced mitophagy in mammalian cells and interact with microtubule-associated protein light chain 3 beta (LC3B) through its LC3 interaction region (LIR). Moreover, the phosphorylation modification of FUNDC1 affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 43 publications
(76 reference statements)
1
101
0
Order By: Relevance
“…23,24 FUNDC1 shows significant impacts on the mitophagy induced by hypoxia in mammalian cells. 25 Another study has also indicated that accumulation of FUNDC1 is presented at the MAM in the hypoxia environment. 26 Furthermore, FUNDC1 was also verified to upregulate in COPD patients, 14 which was consistent with the findings in this study.…”
Section: Discussionmentioning
confidence: 98%
“…23,24 FUNDC1 shows significant impacts on the mitophagy induced by hypoxia in mammalian cells. 25 Another study has also indicated that accumulation of FUNDC1 is presented at the MAM in the hypoxia environment. 26 Furthermore, FUNDC1 was also verified to upregulate in COPD patients, 14 which was consistent with the findings in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Y113C was recently shown to inhibit the enzymatic activity of Atg7 (E1-like enzyme) but not the E2-like activity (Nuta et al, 2018). Mutations at K49 alter the binding to the phosphorylated variants of the LIR-containing LC3B interactor, FUNDC1 (Lv et al, 2016), whereas if this residue is mutated to alanine can increase the binding of another LIR-containing protein, i.e. Nix (Rogov et al, 2017).…”
Section: Classification and Impact Of Lc3b Missense Mutationsmentioning
confidence: 99%
“…Several three-dimensional (3D) structures of LC3B have been solved by X-ray or NMR in the free state (Kouno et al, 2005;Rogov et al, 2013) or in complex with different biological partners (Ichimura et al, 2008;Jemal et al, 2011;Kuang et al, 2016b;Kwon et al, 2017;Lv et al, 2016;McEwan et al, 2015;Olsvik et al, 2015;Qiu et al, 2017;Rogov et al, 2017Rogov et al, , 2013Stadel et al, 2015;Suzuki et al, 2014;Yang et al, 2017). This provides a valuable source of information for investigations using biomolecular simulations and other structural computational methods of both the LC3B wild-type and its mutated variant.…”
Section: Introductionmentioning
confidence: 99%
“…ULK1, as the other major regulator, was shown to be recruited to fragmented mitochondria under hypoxia and to phosphorylate Ser17 of FUNDC1, enhancing the binding to LC3 (Wu et al, 2014b). Although these phosphorylation sites are just a few residues apart, their impact on the interaction of the protein to LC3 is remarkable and the structural basis of this interaction was intensively studied (Lv et al, 2017).…”
Section: Fundc1mentioning
confidence: 99%